Dual-resolution dose assessments for proton beamlet using MCNPX 2.6.0. (November 2015) - Chao, T.C.; Wei, S.C.; Wu, S.W.; Tung, C.J.; Tu, S.J.; Cheng, H.W.; Lee, C.C.
Abstract: The purpose of this study is to access proton dose distribution in dual resolution phantoms using MCNPX 2.6.0. The dual resolution phantom uses higher resolution in Bragg peak, area near large dose gradient, or heterogeneous interface and lower resolution in the rest. MCNPX 2.6.0 was installed in Ubuntu 10.04 with MPI for parallel computing. FMesh1 tallies were utilized to record the energy deposition which is a special designed tally for voxel phantoms that converts dose deposition from fluence. 60 and 120 MeV narrow proton beam were incident into Coarse, Dual and Fine resolution phantoms with pure water, water–bone–water and water–air–water setups. The doses in coarse resolution phantoms are underestimated owing to partial volume effect. The dose distributions in dual or high resolution phantoms agreed well with each other and dual resolution phantoms were at least 10 times more efficient than fine resolution one. Because the secondary particle range is much longer in air than in water, the dose of low density region may be under-estimated if the resolution or calculation grid is not small enough. Highlights: 60 and 120 MeV narrow proton beam in Coarse, Dual and Fine phantoms. Phantoms consisted of pure water, water–bone–water, and water–air–water. Coarse usually under-dose owing to partial volume effect. Dual agrees well with fine but is 10 times faster. Possible under-dose in low density region if resolution is not enough.